Fairness, Adverse Selection, and Employment Contracts - Ferdinand von Siemens (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
This paper considers a firm whose potential employees have private information on both their productivity and the extent of their fairness concerns. Fairness is modelled as inequity aversion, where fair-minded workers suffer if their colleagues get more income net of production costs. Screening workers with equal productivity but different fairness concerns is shown to be impossible if both types are to be employed, thereby rendering the optimal employment contracts discontinuous in the fraction of fair-minded workers. As a result, fairness might influence the employment contracts of all workers although only some are fair-minded, and identical firms facing very similar pools of workers might employ very different remuneration schemes.
urn:nbn:de:bvb:19-epub-13492-6
Keywords: C70; D21; D42; D63; D82; J31; 330; Fairness; Employment Contracts; Adverse Selection; Screening; Heterogeneity in Organizational Form